2005
DOI: 10.1211/0022357055795
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magnesium aluminium silicate on rheological, release and permeation characteristics of diclofenac sodium aqueous gels in-vitro

Abstract: The effect of magnesium aluminium silicate (MAS) on rheological, release and permeation characteristics of diclofenac sodium (DS) aqueous gels was investigated. DS aqueous gels were prepared using various gelling agents, such as 15% w/w poloxamer 407 (PM407), 1% w/w hydroxypropylmethylcellulose (HPMC), and 1% w/w high and low viscosity grades of sodium alginate (HV-SA and LV-SA, respectively). Different amounts of MAS (0.5, 1.0 and 1.5% w/w) were incorporated into the DS gels. Incorporation of MAS into the DS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…This indicated that not only the diffusion process of carbamazepine but also the swelling of the polymers controlled the release of carbamazepine from the gel. The results were in agreement with the release of diclofenac sodium from gel prepared using poloxamer 407 and hypromellose (Pongjanyakul et al 2005). The time taken for release of 50% of the drug (t50%) was 48 min.…”
Section: In-vitro Release Of Carbamazepinesupporting
confidence: 83%
“…This indicated that not only the diffusion process of carbamazepine but also the swelling of the polymers controlled the release of carbamazepine from the gel. The results were in agreement with the release of diclofenac sodium from gel prepared using poloxamer 407 and hypromellose (Pongjanyakul et al 2005). The time taken for release of 50% of the drug (t50%) was 48 min.…”
Section: In-vitro Release Of Carbamazepinesupporting
confidence: 83%
“…The MAS dispersion possessed a basic pH, and its zeta potential was found to be −44.7 mV (Table I). The addition of MAS into the polymer dispersions caused an obvious increase in the pH because of a mild alkalinity of OH groups associated with Si, Mg, and Al in MAS (11). The basic pH of the composite dispersions suggested that SCMC, SA, and MAS also presented negatively charged molecules.…”
Section: Characterization Of Polymer-mas Dispersionsmentioning
confidence: 99%
“…Therefore, MAS has been widely used as a pharmaceutical suspending and stabilizing agent (4). In addition, the positively charged edges on the layers of MAS could interact with anionic polymers such as xanthan gum (9), carbomer (10), and sodium alginate (SA) (11,12), resulting in viscosity synergism and an increase in the thixotropic properties of polymeric dispersions. To obtain similar results, MAS was also used in combination with sodium carboxymethylcellulose (SCMC) for improving not only physical stability (13) but also the flow behavior of suspensions (3).…”
Section: Introductionmentioning
confidence: 99%
“…Upon hydration, its weakly positive edges are attracted by the negatively charged faces, such that the attraction of face-to-edge creates a three-dimensional structure and charges on the layers of MAS will interact with anionic polymers [28,29], resulting in a viscosity synergism. In a recent study [30,31], MAS was used to improve the rheological properties of NaAlg gel. We realize that NaAlg with MAS particles can form a microcomposite film with improved mechanical properties to retard the water uptake as well as drug permeability.…”
Section: Introductionmentioning
confidence: 99%